The Impact Of Compensation, Leadership And Motivation As Mediation On Employee Performance: A Study Of Arthenis Travel Corporation - Utomo, Priyo; Devangga Putra Adhitya Pratama (Jurnal Ekonomi, 2024)
This research investigates the influence of compensation and leadership on employee performance at Arthenis Travel Corporation. The study employs a quantitative approach, utilizing path analysis to explore direct and indirect relationships among these variables. Findings reveal that both compensation and leadership significantly enhance performance, with path coefficients of 0.513 and 0.402, respectively. Compensation, perceived as fair and competitive, motivates employees, leading to higher performance levels. Effective leadership practices, characterized by clear communication and support, also directly boost performance. Moreover, the study examines the mediating role of motivation. Results indicate that motivation partially mediates the relationship between compensation and performance, emphasizing the importance of intrinsic motivation alongside extrinsic rewards. However, motivation does not significantly mediate the relationship between leadership and performance, suggesting that the direct effects of leadership are more impactful. The research aligns with Herzberg's Two-Factor Theory and transformational leadership theories, providing practical insights for organizational strategies. By maintaining competitive compensation structures and investing in leadership development, Arthenis Travel Corporation can enhance employee satisfaction and performance. The study underscores the necessity of a holistic approach that integrates fair compensation and effective leadership to foster a motivated and high-performing workforce, ensuring sustained success in the travel industry.